If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5500 = 9250 + -60(50t) Remove parenthesis around (50t) 5500 = 9250 + -60 * 50t Multiply -60 * 50 5500 = 9250 + -3000t Solving 5500 = 9250 + -3000t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '3000t' to each side of the equation. 5500 + 3000t = 9250 + -3000t + 3000t Combine like terms: -3000t + 3000t = 0 5500 + 3000t = 9250 + 0 5500 + 3000t = 9250 Add '-5500' to each side of the equation. 5500 + -5500 + 3000t = 9250 + -5500 Combine like terms: 5500 + -5500 = 0 0 + 3000t = 9250 + -5500 3000t = 9250 + -5500 Combine like terms: 9250 + -5500 = 3750 3000t = 3750 Divide each side by '3000'. t = 1.25 Simplifying t = 1.25
| 38-8a=6-8(1-4a) | | R/3.=40 | | 22•cos(x/18) | | 2p-5=3p-11 | | 18/(9/7) | | 4p-9=-7+3p | | 7p-28=-21+6p | | 164=0.93(x^2)+2.2x+130 | | 9(3x+6)= | | (5x+12)+(6x-10)=360 | | 2x-5=6x-14 | | Fx=2x^2-3x+1 | | Y=-2(x-(1+I))(x-(1-I)) | | 5w+b=-4-5w | | X-.90x=72 | | 2f-g=5e | | 1/3p=14 | | -30cot^2(x)+15cot(x)-120=0 | | 5w+b=-4-5w-2 | | (4a+12)(5a-20)=0 | | .75a+7=a-1 | | 5(x+2)-(x-5)(x-5)=(2x-3)(2x+3)+19 | | 5x+45=x+21 | | a=p-nt | | -8(4n+3)=30-5n | | 3z+3z=5z+5 | | 1.6(2.2)2x=4(4.1)x | | 18(2.1)x=(6.6)x | | .90x+72=y | | p^3(36p^2q^8)^(1/2) | | -2/-(3/8) | | 72=.90x |